ARTIFICIAL INTELLIGENCE AS A HUMAN SUBSTITUTION? CUSTOMER'S PERCEPTION OF THE CONVERSATIONAL USER INTERFACE IN BANKING INDUSTRY BASED ON UTAUT CONCEPT - Bagana, Batara Daniel; Irsad, Moch; Santoso, Ignatius Hari (Review of Management and Entrepreneurship, 2021)
This study aims to analyze the differences in perceptions between customers of Bank Rakyat Indonesia, Bank Negara Indonesia, and Bank Mandiri regarding the use of the conversational user interface owned by each bank. This study used 58 respondents. By using the Kruskal Wallis technique, it can be concluded that there are differences in perceptions between customers of Bank Rakyat Indonesia, Bank Negara Indonesia and Bank Mandiri who interact using the conversational user interface facility. Even though it is easy to use, the absence of recommendations from the community and family as well as concerns that the chatbot is unable to provide the right information and solutions can have implications for the reluctance of customers to use these facilities in the future